Should a Minimum Number of Members be Required for the Establishment of Enterprise Unions? - Saco Barrios, Raúl (2004)
In labour law, the formation of trade unions is an essential right for workers, insofar as it enables them to obtain representation and protection of their interests. However, a number of questions arise on this issue. For example, what is the minimum number of members required to form a trade union? More importantly, can the exercise of the fundamental right to organise be made conditional? This paper discusses the requirement of a minimum number of members for the formation of company unions. Although the author is emphatic in pointing out that a minimum number should not be required because such a situation ends up affecting the right to organise, he also recognises that the minimum number of twenty affiliated workers, which is recognised in the current regulations, should continue to be maintained, albeit temporarily. This position is adopted after an exhaustive review of the state of the question, which includes a study of the international normative framework, the doctrinal assessment, and other relevant points that allowed us to address and offer a better understanding of this problem.